2009
DOI: 10.1088/0953-8984/21/17/174208
|View full text |Cite
|
Sign up to set email alerts
|

Photodetectors based on intersubband transitions using III-nitride superlattice structures

Abstract: We review our recent progress on the fabrication of near-infrared photodetectors based on intersubband transitions in AlN/GaN superlattice structures. Such devices were first demonstrated in 2003, and have since then seen a quite substantial development both in terms of detector responsivity and high speed operation. Nowadays, the most impressive results include characterization up to 3 GHz using a directly modulated semiconductor laser and up to 13.3 GHz using an ultra-short pulse solid state laser.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 77 publications
0
22
0
Order By: Relevance
“…The AFM analysis showed a root-mean-square surface roughness of about 0.6 nm in an area of 2.5 Â 2.5 "m 2 . From the analysis of the TEM picture, we concluded that the AlN/ GaN interfaces are abrupt at the monolayer scale [36].…”
Section: Fabricationmentioning
confidence: 93%
“…The AFM analysis showed a root-mean-square surface roughness of about 0.6 nm in an area of 2.5 Â 2.5 "m 2 . From the analysis of the TEM picture, we concluded that the AlN/ GaN interfaces are abrupt at the monolayer scale [36].…”
Section: Fabricationmentioning
confidence: 93%
“…But uncertainty in material parameters, the lattice mismatch between AlN and GaN, the relaxation peculiarities of wurtzite nitride materials, and the presence of internal pyro-and piezo-electric fields make the simulation of this system only a design guideline but not any kind of valid confirmation of the energy eigen values i.e. absorption spectra [11].…”
Section: Design Conceptmentioning
confidence: 99%
“…AlGaN/GaN multiple quantum well (MQW) structures grown on GaN/sapphire templates (GaN templates) have attracted much interest for intersubband (ISB) transition devices operating in the near-infrared and mid-infrared spectral ranges, such as photovoltaic and photoconductive GaN/AlN quantum well (QW) detectors [1] and electrooptical modulators [2], benefiting from the large conduction-band offset (1.75 eV) between GaN and AlN. In addition, material transparency in a wide spectral region (360 nm to 13μm for GaN) [3], large longitudinal-optical phonon energy (92 meV for GaN), and the rather heavy-electron effective mass (0.22 × m 0 for GaN) also guarantee the realization of ISB transitions at room temperature.…”
Section: Introductionmentioning
confidence: 99%